(untitled) (Romanian Biotechnological Letters, 2025)
Aging is defined as a progressive loss of function, leading to reduced fertility, increased mortality, and disability [1]. Lifespan and healthspan are influenced by both genetic and environmental factors, and recent studies have shown that aging can be modulated in model organisms through genetic inter- ventions [3]. In C. elegans, mutations in the daf-2 insulin/IGF-1 receptor and odr-3 G-protein-coupled receptor significantly extend lifespan, with the daf-2; odr-3 double mutant showing synergistic effects beyond single mutants [2][3]. To expand this, we investigated the orthologous genes in Drosophila melanogaster: InR (insulin receptor) and GαO (G-protein alpha O subunit), using both single and double mutants. We found that both InR and G𝛼O mutants extended lifespan compared to wildtype, however, the GαO;InR double mutant showed only a slight increase in lifespan compared to the InR mutant, less pronounced than the synergy observed in C. elegans. These findings suggest that while these genes may have conserved roles in lifespan regulation, their interactions differ between species, indicating species-specific modulation of aging.